Elucidating Reasons for Resident Underutilization of Electronic Adverse Event Reporting. (July 2016) - Hatoun, Jonathan; Suen, Winnie; Liu, Constance; Shea, Sandy; Patts, Gregory; Weinberg, Janice; Eng, Jessica
Reasons for resident underutilization of adverse event (AE) reporting systems are unclear, particularly given frequent resident exposure to AEs and near misses (NMs). Residents at an academic medical center were surveyed about AEs/NMs, barriers to reporting, patient safety climate, and educational interventions. A total of 350 of 527 eligible residents (66%) completed the survey; 77% of respondents reported involvement in an AE/NM, though only 43% had used the reporting system. Top barriers to reporting were not knowing what or how to report. Surgeons reported more than other residents (surgery, 61%; medical, 38%; hospital-based, 15%; P < .01), yet more often felt that systems were unlikely to change after reporting (surgery, 49%; medical, 28%; hospital-based. 18%; P < .01). Residents preferred discussions with supervisors (52%) and department-led conferences (46%) to increased reporting. Efforts to increase resident reporting should address common barriers to reporting as well as department-specific differences in resident knowledge, perceptions of system effectiveness, and educational preferences.